A Banking Union for the Euro Area - Goyal, Rishi (Staff Discussion Notes; Staff Discussion Notes ;, 2013)
The SDN elaborates the case for, and the design of, a banking union for the euro area. It discusses the benefits and costs of a banking union, presents a steady state view of the banking union, elaborates difficult transition issues, and briefly discusses broader EU issues. As such, it assesses current plans and provides advice. It is accompanied by three background technical notes that analyze in depth the various elements of the banking union: a single supervisory framework; a single resolution and common safety net; and urgent issues related to repair of weak banks in Europe.